PUISI BERBASIS HASIL KARYA GAMBAR: UPAYA PENGUATAN LITERASI SISWA SD KELAS TINGGI - Heri Setiawan; Styo Mahendra Wasita Aji; Abdul Aziz (Inteligensi : Jurnal Ilmu Pendidikan, 2019)
This study aims to examine and analyze the learning of writing poetry based on students' work drawings as an effort to strengthen the literacy of high grade elementary students. The method used is literature review by analyzing several studies related to the topic of discussion, namely literacy, drawing in elementary school, and poetry in the elementary school curriculum. From the results of the study produced a synthesis that shows that in primary school, literacy development still pivots on literacy reading. The ideas generated based on studies are developing fun writing literacy learning through writing "Poetry Based on Artwork" with the main steps: (1) determining the theme of the picture; (2) theme exploration; (3) drawing activities; (4) list beautiful words based on the drawings made (prewriting); (5) composing a framework of poetry (drafting); (6) developing poetry (writing); (7) editing and improving poetry (revising editing); and (8) reading the final poem arranged based on pictures (publishing). This activity is expected to strengthen the literacy of high class students with learning that combines drawing, poetry, writing, and communicating writing results holistically and pleasantly.